EFEKTIVITAS PENGGUNAAN SMARTPHONE DALAM AKTIVITAS BELAJAR MAHASISWA ILMU KOMUNIKASI UNIVERSITAS SLAMET RIYADI SURAKARTA - Nurnawati Hindra H, Egie Apriani Putri, Dian Esti Nurati & (Transformasi, 2016)
New technologies in the form of communication is often known as smartphones. Communicationtechnologies in the form of a smartphone is a phenomenon of the most unique and interesting inits use. Smartphone that is easy to carry anywhere now no longer know the ages and walks oflife, even called now smartphones have become "technological populist". The phenomenon thatoften happens today is not uncommon people prefer to play or use the smartphone when thelearning process takes place. This study aim to determine the effectiveness of using asmartphone to learn students activity of Communication Studies University of Slamet RiyadiSurakarta. The results showed that the effectiveness of the use of smartphones is perceived bystudents in learning activities. However, the use of smartphones also cause two effects, namelythe positive impact that provides ease in finding the course material with the smartphone. Thenegative effect is that students become lazy learn from relying on the smartphone.Key words: effectiveness of smartphones and learning activities